HEAVY METAL ACCUMULATION IN THE EDIBLE LEAFY PARTS OF AFRICAN NIGHTSHADE (Solanum Scabrum Mill) IRRIGATED WITH VARYING WATER QUALITY - Kamande, Peter Ngugi; Kabuyah, Dr. Rachel, . N; Ndunda, Dr. Ezekiel (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
This experimental study was carried out to assess how heavy metals accumulates in the edible leafy parts of African nightshade (Solanum Scabrum Mill) irrigated with varying water quality. Different types of water used included wastewater, tap water, water from shallow wells and from borehole. The experiment was carried out under randomized complete block design (RCBD) with four replications. From the results, crop samples grown using deep well registered the highest mean value in regard to Zn2+, Mn2+ and Pb2+ concentration at 37.17 (3.70), 10.63 (0.48) and 8.49 (0.35) ppm respectively. Low concentration of heavy metals Pb2+, Cu2+ and Cd2+ at 4.36 (0.40), 3.98 (0.20) and 2.09(0.12) respectively was detected in crops samples grown using tap water. This is an indication that tap water possess ability to flush out the toxins in the soils. As compared to the WHO standards, the values of Cd2+ and Pb2+ were significantly above the recommended limits across all the blocks for the plant samples which will result to bioaccumulation in the long run.